Pengaruh Kemudahan, Kepercayaan dan Keamananan Pengguna Media Sosial Whatsapp Terhadap Minat Beli Konsumen Pada Mahasiswa Fakultas Ekonomi Dan Bisnis, Universitas Malikussaleh Di-Lhokseumawe - Mahpriza Putra; Nurainun Nurainun (Jurnal Visioner & Strategis, 2021)
This study aimed to identify and analized the effect of ease, trust, and safety of WhatsApp application users as a medium for online shopping on consumer purchase interest. The sampling method used was a purposive method with a total sample of 120 respondents. The method of data analysis used was simple linear regression analysis. The results show that convenience positively and significantly influenced consumer purchase interest because WhatsApp is easy to learn, controllable, understandable, flexible, easy to become proficient, and easy to use. Trust positively and significantly influenced consumer purchase interest because consumers believe that transacting through WhatsApp media is safe in, safe in product guarantees, and consumers know the seller's reputation. Security positively and significantly influenced consumer purchase interest because WhatsApp media is safe in transactions, transactions via WhatsApp media are easy, proof of safe transactions is sent via WhatsApp media, and products as expected shopping through WhatsApp media.